Antioxidant Activity Test of Ethanol Extract of Ripe and Young Cocoa Pods (Theobroma Cacao L.) - Andriana Andriana; Minarni R. Jura (Universitas Tadulako, 2022)
Antioxidant activity test of Ethanol Extract of Ripe and Young Cocoa Pod Skin (Theobroma Cacao L.) with DPPH (1,1-diphenyl-2-picrylhydrazyl) using UV-Vis spectrophotometer has been carried out. This study aimed to determine the IC50 value of the ethanol extract of ripe cocoa pods and young cocoa pods (Theobroma Cacao L.). The mature and young cocoa pods were extracted using absolute ethanol solvent and tested for their antioxidant activity using DPPH (1,1-diphenyl-2-picrylhydrazyl). The concentration variations used in the ethanol extract of ripe cocoa pods and young cocoa (Theobroma Cacao L.) were 20 ppm, 40 ppm, 60 ppm, and 80 ppm. The results showed that the IC50 values of the ethanol extract of ripe and young cocoa pods were 76.094 ppm and 91.884 ppm, respectively. Meanwhile, the IC50 value of vitamin C compared was 63.519 ppm. Based on the IC50 value data above, it can be seen that the antioxidant activity of the ethanol extract of young cocoa pods and ripe cocoa pods are potent antioxidants.